Akta polskich organizacji, stowarzyszeń i związków przechowywane w zasobie Archiwum Państwowego w Bydgoszczy (Kronika Bydgoska, 2021)
Files of Polish organizations, associations and societies account for only a small percentage of archives held at the National Archives in Bydgoszcz. Their conservation status in terms of quantity varies, limiting research possibilities concerning their structure and activity. Files of every organization, association and society create an independent archival group. Each of them has been provided with information on archival support making possible navigation among archives. Files that are stored only in part are included in a collection of remnants, comprising files of several organizations that have remained in a residual form. All information on archives presented are available in an online version on the portal Search in Archives available on the website of the National Archives in Bydgoszcz. The presented files, despite their residual nature, frequently serve as unique historical sources; however, they encourage expansion of searches by complementary archives containing important information on many organizations, associations and  societies, e.g. files of state administration authorities and bodies due to their role in supervision over activity.